ASCETICISM POETRY BETWEEN IMAM SHAFI'I AND ABU AL-ATAHEYA A COMPARATIVE STUDY - Kouyate, Sekou (UIR Press, 2021)
The research aims to compare the two poets in terms of social, religious, cultural, economic, and psychological factors and then talk about the similar poetic contents of both poets within the framework of ascetic poetry. The researcher used the French school curriculum, in which the comparison is made between literature that is related to each other based on impact and influence. The most prominent result of the study was that Abu Al-Atheya was influenced by imam shafi'i in some aspects of his poem, but he invented and mastered it perfectly.